Material intensity of advanced composite materials: Results of asudy for the Verbundwerkstofflabor Bremen e.V. - Hartmut Stiller (Wuppertal Institut für Klima, Umwelt, Energie, 1999)
In this paper the results of an analysis of the material intensity of advanced composite materialsare presented. The analysis is based on the MIPS-concept of the Wuppertal Institute whichallows the calculation of the overall material intensity of products and services. It can be shownthat the production of one kg of E-Glass fibers is connected with the consumption of 6.2 kgmaterials, 95 kg water and 2.1 kg oxygen which is of similar size compared to the inputsrequired in steel production. Material inputs required to produce one kg of p-aramid are 37 kg ofmaterials and 19.6 kg air. Values for carbon fibers are even higher yielding to 61.1 kg of abioticmaterials and 33.1 kg of air. Similarly, the production of epoxy resins is connected with largermaterial flows than the production of polyester resins. Of core materials, inputs per kg for PVC-foam exceed those in PUR-foam production by a factor of 1.4 in water to 2.3 in abiotic materialconsumption.However, ecologically decisive are not the inputs per kg but the material input per service unit.Therefore, the material input per service unit computed for the body of a passenger ship and arobot arm are compared with alternative steel and aluminium versions. Both examples show thatin the case of significant inputs during the user phase of products, even a more materialintensive investment in the production phase can yield significant ecological benefits over thewhole life-cycle compared to metal versions. Improvements can easily reach a factor of twoalbeit significant potential for engine optimizations have still been neglected.Results already include the actual recycling quota of metals whereas for composites only virginmaterial has been calculated as any form of real recycling does not actually exist but only certaintypes of downrecycling. Of those treatment options, first material recycling and second the usein blast furnaces would lead to better results in resource productivity than incineration andlandfills.The paper finally draws some conclusions about the potential advantages of material substitutionin the automotive industry. Due to the rather short real operation time of cars during their userphase - around six months - an investment in advanced composite materials in car productiononly results in a significant improvement of the overall eco-efficiency of cars if it allows asubstantial weight reduction of the overall vehicle.
urn:nbn:de:bsz:wup4-opus-9268
Keywords: 330